2017
DOI: 10.3174/ajnr.a5074
|View full text |Cite
|
Sign up to set email alerts
|

Application of Time-Resolved 3D Digital Subtraction Angiography to Plan Cerebral Arteriovenous Malformation Radiosurgery

Abstract: BACKGROUND AND PURPOSE:Time-resolved 3D-DSA (4D-DSA) enables viewing vasculature from any desired angle and time frame. We investigated whether these advantages may facilitate treatment planning and the feasibility of using 4D-DSA as a single imaging technique in AVM/dural arteriovenous fistula radiosurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…To date, few studies examining the efficacy of RA in GKS have been reported, and no detailed analyses of dosimetric variables like those performed herein have been performed previously. 6,30 Our findings support the use of RA in GKS planning; however, further research aimed at determining whether the use of RA improves the radiosurgical outcomes, including the rates of nidus obliteration and complications, is needed. The actual efficacy of RA seems to vary depending on the characteristics of the nidus.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…To date, few studies examining the efficacy of RA in GKS have been reported, and no detailed analyses of dosimetric variables like those performed herein have been performed previously. 6,30 Our findings support the use of RA in GKS planning; however, further research aimed at determining whether the use of RA improves the radiosurgical outcomes, including the rates of nidus obliteration and complications, is needed. The actual efficacy of RA seems to vary depending on the characteristics of the nidus.…”
Section: Discussionmentioning
confidence: 55%
“…27,28,37 Although it is likely that the integration of RA would improve GKS dose planning, few studies examining the efficacy of integrating RA into the GKS treatment planning process have been performed. 6,30 At our institution, we have routinely used RA for GKS planning since 2015. Therefore, the aim of the present study was to examine the efficacy of integrating RA into the dose planning process for AVM treatment.…”
mentioning
confidence: 99%
“…Moreover, very few studies have described the effectiveness of 3DRA on GKRS planning, though they do not state a detailed integration method. [19][20][21] Thus, most physicians still cannot benefit from 3DRA. Here, we show a very simple method to integrate 3DRA into GKRS planning.…”
Section: -9mentioning
confidence: 99%
“…Recent reports have demonstrated the usefulness of 4D‐DSA both in analyzing the details of complex vascular lesions and in treatment planning . The high frame rate of the acquisitions (30 fps) combined with the high spatial resolution of the x‐ray detector combine to provide images that allow visualization of minute changes in flow patterns and angio‐architecture …”
Section: Introductionmentioning
confidence: 99%
“…10,11 The high frame rate of the acquisitions (30 fps) combined with the high spatial resolution of the x-ray detector combine to provide images that allow visualization of minute changes in flow patterns and angio-architecture. 10,11,12 In preliminary studies, we have shown that, through use of a Fourier Phase technique, it is possible to obtain values of blood velocity using 4D-DSA data that are in agreement with data obtained using a doppler flow wire. 13 In this report we describe and illustrate further development and testing of this approach.…”
Section: Introductionmentioning
confidence: 99%